Intercultural Competence - Way to Solve the Problems of Today's World - Roxana DOROBANȚU-DINA (Eastern European Journal of Regional Studies, 2021)
Abstract: This article highlights the need to form intercultural competence, which is closely in line with the dynamics of globalization and migration - so much publicized in recent years. Intercultural education is the study discipline included in the Romanian National Curriculum starting with 2017, which is taught in the sixth grade, this being the alternative to open communication, understanding, tolerance, interaction, solidarity and intercultural dialogue between people - regardless of ethnicity, race, religion, social condition, etc. Based on theoretical and praxiological analysis regarding the formation of the intercultural competence to the students from the gymnasium classes, three stages imposed in the finalization of the pedagogical experiment are completed: finding, training and verification. The added value of the scientific research paper is supported by teacher training activities based on the theme presented, through the elaboration and application of the Initiation Guide in Education and Intercultural Competence. Increased attention was paid to the theoretical-applied foundations that formed the basis for the elaboration and application of the Pedagogical Model for the formation of intercultural competence to the students from the gymnasium classes.